Exploring the relationship between Total Athleticism score and CrossFit® Open Performance in amateur athletes: single measure involving body fat percentage, aerobic capacity, muscle power and local muscle endurance - Ramires Alsamir Tibana; Fábio Hech Dominski; Alexandro Andrade; Nuno Manuel Frade de Sousa; Fabricio Azevedo Voltarelli; Ivo Vieira de Sousa Neto (European Journal of Translational Myology)
There has been an increasing interest among CrossFit® coaches and practitioners in identifying indicators of sport performance. This study aimed to examine the correlation between anthropometric measures, cardiorespiratory capacity, power, local muscle endurance, and total athleticism score, with performance in the CrossFit® Open 2021. Fourteen male volunteers (aged 30.3 ± 5.8 years) participated in the study and underwent a series of tests on separate weeks. These tests included assessments of body fat percentage (subcutaneous adipose thickness measured at seven sites), maximal oxygen consumption (2 km test in rowing ergometer), muscle power (one repetition maximum in power clean), and muscle endurance (Tibana test, which included the conclusion of four distinct rounds of work). These results were used to calculate the total score of athleticism, which was then compared to the participants performance during the CrossFit® Open 2021. The athletes presented an average of body fat (8.6 ± 2.0%), maximal oxygen consumption (53.3 ± 2.4 mL. (kg.min)-1), 2km row time (07:00 ± 00:21 mm:ss), 1-Repetition maximum in power clean (125.2 ± 21.2 kg) and Tibana test performance (281.0 ± 35.9 repetitions). Interestingly, the top five athletes with the highest scores also achieved the highest z-scores in the CrossFit® Open 2021. Conversely, the four athletes with the lowest TSA score had the lowest z-scores in the CrossFit® Open. Moreover, almost perfect correlation (r = 0.91; p<0.01) was found between the total athleticism score and z-scores in the CrossFit® Open 2021. The total score may be a single measure and holistic indication of athleticism level in CrossFit®. Furthermore, coaches can potentially apply this useful tool for monitoring athletic performance and designing training sessions that address specific areas of CrossFit® performance.